The Effect Of Transformational Leadership, Work Environment And Organizational Citizenship Behavior On Work Satisfaction And Its Implications To The Quality Of Service (Study In Some Private School In Banten Province). - Purnawan, Yohan; Jasfar, Farida; Hady, Hamdy (Archives of Business Research, 2019)
The purpose of this study is to develop and test the conceptual model of the effects betweeen transformational leadership, work environment and organizational citizenship behavior on job satisfaction and its implications for service quality in the private secondary school education industry. This research was conducted through a survey of teachers in several private schools in Banten province with a sample of 445 respondents. Premiere data is done by random sampling method, and data analysis uses Structural Equation Model and Multivariate Analysis. Data is processed with AMOS 22.0 to test the concept of the model and hypothesis. This research tries to look at the transformational leadership, work environment and organizational citizenship behavior towards job satisfaction and its implications for service quality provided by high school teachers in several private schools in Banten Province. The findings in this study are that service quality is influenced quite positively and significantly by transformational leadership, work environment, organizational citizenship behavior and job satisfaction. In Job satisfaction it is influenced quite high by transformational leadership, work environment and organizational citizenship behavior. This means that the better transformational leadership, work environment and organizational citizenship behavior, the higher job satisfaction will be. Job satisfaction is influenced most strongly by organizational citizenship behavior, while service quality is influenced most strongly by the work environment. Found 7 hypotheses accepted and 2 hypotheses rejected. This research provides a theoretical contribution in the form of service quality model and provides managerial implications for the formal education industry, especially private secondary schools. This study was limited to secondary school teachers in private schools in Banten Province. The research activity was carried out in 4 major cities including Cilegon, Serang, Tangerang, South Tangerang.